Konsep Dan Implementasi 3 Pilar Deep Learning Pada Pendidikan Dasar - Izza Umami; Ahmad Susanto (Asosiasi Dosen Peneliti Ilmu Keislaman dan Sosial, 2025)
Abstract The transformation of education in the era of the Merdeka Curriculum demands a deeper, more meaningful, and enjoyable learning approach. This article discusses the concept and implementation of the three pillars of deep learning—mindful learning, meaningful learning, and joyful learning—which serve as the foundation of 21st-century education. These three pillars are examined as alternatives to surface learning approaches that tend to be shallow and memorization-oriented. This study employs a literature review method, drawing on relevant national and international sources, including recent research findings. The results indicate that applying deep learning in primary education can enhance critical thinking skills, foster active student engagement, and connect learning to real-life contexts. However, challenges in implementation remain, particularly in aspects such as teacher competency, infrastructure, and the readiness of students and parents. This article recommends strengthening teacher capacity, reformulating the curriculum, and integrating technology as strategic solutions. Keywords: Deep Learning, Merdeka Curriculum, Mindful Learning, Meaningful Learning, Joyful Learning, Primary Education.